INTERNAL CONTROL IN THE PUBLIC SECTOR IN INDONESIA: A CASE STUDY OF STATE TAX RECEIVABLES MANAGEMENT - Asqolani Asqolani; Rahmat Taufik Hidayat; Marsono Marsono; Bayu Kalpikotomo (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract— This research focuses on the Internal Control System (SPI) in managing tax collection at the Directorate General of Taxes (DGT). This study is concerned with the effectiveness of internal control in the public sector, especially on the revenue administration of the central government, which is also stated in the Audit Agency (BPK) report. Internal control is vital to maintain the reliability of financial information in an organization. The method used is qualitative, using The DGT as a case study. The novelty of this research lies in its focus on the tax receivable from both internal and the auditor's points of view. Interviews were conducted with the DGT, the Financial Audit Agency (BPK), and the Inspectorate General (Inspektorat Jenderal/Itjen). Data comes from the Central Government Financial Statements (Laporan Keuangan Pemerintah Pusat/LKPP) and Audit Reports (Laporan Hasil Pemeriksaan/LHP). The results of this study show that the SPI in managing tax collection is good, but there is still room for improvement. It is expected that some recommendations for improving the SPI, such as improving the issuance of letters for the implementation of tax receivables to be entirely through the system, limiting the materiality of collecting tax receivables, maximizing tax collections, especially those that will expire, adding an early warning system to detect overdue collections, faster solving suspend data, and data integration, especially with the tax court for appeal decisions and commercial courts for registration of tax receivables to curators. Keywords: Audit Report; Central Government Financial Report (LKPP); Internal Control System; Tax Receivables.